Design of Video Detection for Drowsy Prevention Based on Car Driving - Byeongtae Ahn (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this paper, a drowsiness prevention system was developed to prevent large-scale disasters in traffic accidents. And drowsiness was predicted using face recognition face recognition technique and eye blink recognition technique, and prediction was improved by applying machine learning to improve drowsiness prediction. Additionally, the CO2 sensor chip was used to detect additional drowsiness prevention. In addition, STT (Speach To Text) was applied using voice recognition technology so that the driver can apply for a desired music or broadcast or make a phone call in order to break drowsiness while driving.